Take the equation ax2+bx+c=0.
In order to factor this equation, you need to find two values d and e where da=ce and d+e=b. This means that d=b−e, which means that b−ea=ce, or that e2−be+ac=0. Similarly, it also means that d2−bd+ac=0.
By applying this process to x2−bx+ac=0 (f(a,b,c)=x2−bx+ac), you end up with x2+bx+ac=0, then back to x2−bx+ac=0. At this point, it just cycles between the two equations.
I haven't thought much about these two equations, but the fact that the equation ax2+bx+c=0 feeds into this 2-cycle seems somewhat strange to me. Can anyone explain why this happens?
#Algebra
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.